Overview Of Knowledge And Motivation Of Pregnant Women In The Iii Trimester Regarding Preparation For Birth In The Working Area Of The Talang Banjar Health Center - Erna Elfrida Simanjuntak (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Based on data from the number of births by health workers in 2024, there are 13,918 with a percentage of 92.7%. This type of research is descriptive research which aims to see a picture of the knowledge and motivation of third trimester pregnant women regarding preparation for childbirth. Population in This study included all 32 pregnant women in the third trimester regarding preparation for childbirth. The sampling technique used in this research was total sampling, namely 32 third trimester pregnant women. Data analysis was carried out univariately with the aim of obtaining an overview of the frequency distribution of each variable studied to facilitate data interpretation. The majority of respondents had sufficient knowledge about childbirth preparation, namely 18 respondents (56%), respondents who had good knowledge about childbirth preparation, namely 12 respondents (38%) and respondents who had poor knowledge, namely 2 respondents (6%). The majority of respondents had good motivation regarding childbirth preparation, namely 22 respondents (69%) and respondents who had poor motivation were 10 respondents (31% ).Public health Office It is hoped that a policy can be made to increase the provision of counseling and counseling to pregnant women regarding childbirth preparation so that it can increase knowledge and good motivation for pregnant women regarding childbirth preparation.